The Influence of Motivation and Self-Efficacy on Work Readiness among Persons with Disabilities in Gresik Regency - Amaliyah Hamduuna; Nur Cahyadi (Fakultas Ekonomi, Universitas Muslim Indonesia, 2026)
This study aims to analyze the influence of motivation and self-efficacy on work readiness among working-age persons with disabilities in Gresik Regency. Although supported by inclusive policies and training programs, work readiness among persons with disabilities continues to face challenges particularly in the psychological domain. This research employs a quantitative approach, utilizing a questionnaire distributed to 70 respondents with disabilities who are work-ready (aged 17 years and above) in Gresik Regency, selected through total sampling. The independent variables are motivation and self-efficacy, while work readiness serves as the dependent variable. Data were analyzed using Structural Equation Modeling (SEM). The results indicate that all constructs meet the required criteria for validity and reliability. The main findings reveal that both motivation and self-efficacy have a positive and significant effect on work readiness among persons with disabilities. Self-efficacy plays a crucial role in strengthening individuals’ self-confidence and resilience, while motivation acts as a key driver in shaping work-related behaviors. The implications of this study underscore the importance of empowerment programs that integrate psychological strengthening alongside technical skill development.